Registration of 'CRIS‐129', an Early‐Maturing, Heat‐Tolerant, and High‐Yielding Cotton Cultivar. Issue 3 (17th August 2017) - Ahsan, Muhammad Zahir; Khan, Muhammad Idrees; Bhutto, Hidayatullah; Anjum, Rehana; Majidano, Muhammad Saffar; Bano, Saira; Soomro, Abdul Wahab; Panhwar, Faiz Hussain; Channa, Abdul Razzaque; Malik, Tassawar Hussain
Abstract : 'CRIS‐129' (Reg. No. CV‐134, PI 682095) is an early‐maturing, high‐yielding, and heat‐tolerant upland cotton ( Gossypium hirsutum L.) cultivar. CRIS‐129 was developed at the Central Cotton Research Institute Sakrand, Pakistan, through conventional breeding (pedigree selection) methods and was the result of a cross between 'CIM‐70' and 'B‐909'. CRIS‐129 performed much better than the commercial cultivars in a series of experiments conducted on cotton research stations and growers' fields. In a 2‐yr National Coordinated Varietal Trial conducted across Pakistan, CRIS‐129 exhibited a broad range of climatic adaptability. In July 2014, it was presented before the Technical Sub‐Committee for Approval of Crop Varieties and Techniques (Director General of Research, Sindh Tandojam) for discussion and recommendations and was approved by the Provincial Seed Council on November 2014 for general cultivation in Sindh Province.